Pickling solution and environment-friendly hot galvanizing process using pickling solution

By adding specific formulas and wetting agents to the pickling solution, the excessive corrosion and environmental safety of the existing pickling solution on the metal matrix are solved, and an efficient and environmentally friendly metal surface cleaning effect is achieved.

CN119530814APending Publication Date: 2025-02-28SHANGHAI JUFENG HOT GALVANIZING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411714545.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing pickling liquid is prone to excessive corrosion to the metal matrix during the metal cleaning process, and poses a threat to operators and environmental safety. The corrosion inhibitor has poor stability and great harm to the environment.

Method used

A pickling solution formula is adopted, including hydrochloric acid, formic acid, nonylphenol polyoxyethyl ether, sodium dodecyl sulfate, sodium carbonate and hexamethylenetetramine, combined with wetting agents such as hydroxyethylene diphosphonic acid, modified gelatin and modified loofah fiber, to adjust the pH value of the pickling solution and improve its wetting and permeability.

Benefits of technology

Effectively remove dirt from metal surfaces, improve cleaning effect and efficiency, reduce foam generation during pickling, improve operating conditions, and protect the metal surface from excessive corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156605870000101
    Figure BDA0005156605870000101
  • Figure BDA0005156605870000111
    Figure BDA0005156605870000111
Patent Text Reader

Abstract

The invention belongs to the technical field of metal material cleaning, and particularly discloses a pickling solution and an environment-friendly hot galvanizing process using the pickling solution. The pickling solution comprises the following raw materials in parts by weight: 30-40 parts of hydrochloric acid, 15-20 parts of formic acid, 1-2 parts of nonylphenol polyoxyethylene ether, 6-10 parts of lauryl sodium sulfate, 2-4 parts of sodium carbonate, 3-5 parts of hexamethylenetetramine, 110-120 parts of water and a wetting agent, the wetting agent comprises 1-hydroxyethylidene-1, 1-diphosphonic acid, modified gelatin and modified loofah sponge fibers. The prepared pickling solution has the advantages of being good in stability and small in environmental harm, dirt on the metal surface can be more effectively removed, and the cleaning effect and efficiency are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal material cleaning, and in particular to a pickling solution and an environmentally friendly hot-dip galvanizing process using the pickling solution. Background Art

[0002] Pickling fluid plays an important role in the industrial field, especially in metal surface treatment, cleaning and rust removal. It is mainly used to remove oxides, rust and other impurities on the metal surface. Common pickling fluids include inorganic acids such as sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, and some organic acids such as acetic acid, acetic acid, lactic acid, etc., which are chemical solutions used for metal surface treatment.

[0003] However, these pickling solutions are prone to excessive corrosion of metal substrates during the metal cleaning process, and also pose great risks to the safety of operators and the environment. In order to reduce the excessive corrosion damage of pickling solutions to metal substrates, amine compound corrosion inhibitors are usually added. Amine compound corrosion inhibitors can form a protective film on the metal surface and effectively slow down the corrosion of the acidic medium to the metal. However, amine compound corrosion inhibitors have problems such as poor stability and great harm to the environment. Summary of the invention

[0004] In order to improve the problems of poor stability and great harm to the environment of corrosion inhibitors, the present application provides a pickling solution and an environmentally friendly hot-dip galvanizing process using the pickling solution.

[0005] The present application provides a pickling solution, which adopts the following technical solution: A pickling solution comprises the following raw materials, measured by weight: 30-40 parts of hydrochloric acid, 15-20 parts of formic acid, 1-2 parts of nonylphenol polyoxyethyl ether, 6-10 parts of sodium dodecyl sulfate, 2-4 parts of sodium carbonate, 3-5 parts of hexamethylenetetramine, 110-120 parts of water, and a wetting agent; the wetting agent comprises hydroxyethylidene diphosphonic acid, modified gelatin, and modified loofah fiber.

[0006] By adopting the above technical solution, hydrochloric acid and formic acid as the basic components of the pickling solution can react chemically with oxides, rust and certain types of dirt on the metal surface to dissolve them. 2 O 3) has a strong dissolving ability. Formic acid, as an auxiliary acid, provides additional dissolving power. Together with hydrochloric acid, it accelerates the dissolution of oxides on the metal surface, thereby improving pickling efficiency. The synergistic combination of nonylphenol polyoxyethyl ether and sodium dodecyl sulfate can reduce the surface tension of water, improve the wettability of the pickling solution on the metal surface, help the pickling solution to cover the metal surface more evenly, and promote the pickling solution to penetrate into the tiny gaps and holes on the metal surface, ensuring that all areas can be exposed to the acid, accelerating the chemical reaction between the acid and the metal oxide, and increasing the pickling speed. In addition, nonylphenol polyoxyethyl ether and sodium dodecyl sulfate can also help disperse and suspend dissolved dirt to prevent it from redepositing on the metal surface.

[0007] Sodium carbonate can react with hydrochloric acid to produce carbon dioxide, water and sodium chloride, which can adjust the pH value of the pickling solution and prevent the acid from being too strong. At the same time, the carbon dioxide bubbles produced can help loosen and remove the dirt on the metal surface. Through the wetting, dispersing and solubilizing effects of the wetting agent, the pickling solution can more effectively remove the dirt on the metal surface and improve the cleaning effect and efficiency. At the same time, the addition of the wetting agent helps to reduce the foam generated during the pickling process and improve the operating conditions. Hexamethylenetetramine helps stabilize the pH value of the pickling solution and prevents drastic changes in the pH value during the cleaning process. Through the chemical dissolution of hydrochloric acid, the buffering and stabilizing effect of hexamethylenetetramine, the wetting, dispersing, penetrating and corrosion inhibition of nonylphenol polyoxyethyl ether and sodium dodecyl sulfate, the pickling solution can more effectively remove the dirt on the metal surface, improve the cleaning effect and efficiency, reduce the foam generated during the pickling process, and improve the operating conditions.

[0008] Among wetting agents, hydroxyethylidene diphosphonic acid has good chelating, corrosion inhibition, dispersion and pH stabilization effects. It can form stable complexes with metal ions to prevent them from redepositing on the metal surface, more effectively remove dirt on the metal surface, and improve the cleaning effect and efficiency. Modified gelatin can be used as a corrosion inhibitor. It forms a protective film on the metal surface to reduce the direct erosion of the acid in the pickling solution on the metal, thereby protecting the metal surface from excessive corrosion, controlling the corrosion rate during the pickling process, and protecting the metal matrix; modified gelatin also has good suspension properties, which can help the solid particles (such as dissolved oxides, rust, etc.) generated during the pickling process to remain suspended, prevent them from redepositing on the metal surface, and ensure the cleaning effect. It can also improve the rheological properties of the pickling solution, make it more evenly distributed on the metal surface, improve the coverage and permeability of the pickling solution, and ensure the consistency and thoroughness of the pickling effect.

[0009] Modified loofah fiber has a natural porous structure and can be used as a physical support material for filtration and support in pickling liquid. During the pickling process, the modified loofah fiber can capture and filter out solid particles dissolved by the pickling liquid, such as metal oxides, rust, etc., to prevent them from redepositing on the metal surface, thereby improving the cleaning effect. The natural components on the surface of the modified loofah fiber, such as cellulose and lignin, can form a protective film on the metal surface, reducing the direct erosion of the acid in the pickling liquid on the metal. Moreover, the porous structure of the modified loofah fiber can increase the contact area of ​​the pickling liquid, help the pickling liquid to be more evenly distributed and penetrated into the metal surface, improve the coverage and permeability of the pickling liquid, and ensure the consistency and thoroughness of the pickling effect.

[0010] Preferably, the wetting agent comprises the following raw materials in parts by weight: 5-8 parts of hydroxyethylidene diphosphonic acid, 3-6 parts of modified gelatin, and 8-10 parts of modified loofah fibers.

[0011] By adopting the above technical solution, the dosage of each component in the wetting agent is further limited, and the components cooperate to improve the cleaning effect of the steel plate. Hydroxyethylidene diphosphonic acid can form a stable complex with metal ions, more effectively remove dirt on the metal surface, and improve the cleaning effect and efficiency. The modified gelatin forms a protective film on the metal surface, reducing the direct erosion of the acid in the pickling solution on the metal, thereby protecting the metal surface from excessive corrosion and protecting the metal matrix; the modified loofah fiber can capture and filter out the solid particles dissolved by the pickling solution to prevent them from being re-deposited on the metal surface, thereby improving the cleaning effect.

[0012] Preferably, the preparation method of the modified gelatin comprises the following steps: (1) adding hydrochloric acid to a gelatin aqueous solution to adjust the pH of the solution to 5-6, then stirring the solution at a temperature of 60-65° C., and adding trimethylamine oxide to obtain a gelatin solution; (2) dispersing graphene oxide in an ammonia solution, adjusting the pH of the solution to 8-9, adding a quaternary ammonium salt, stirring the reaction, centrifuging, and drying to obtain quaternary ammonium salt-modified graphene oxide; (3) dispersing the quaternary ammonium salt-modified graphene oxide of step (2) in the gelatin solution of step (1), adding modified starch, stirring at a temperature of 65-70° C. for 1-2 h, drying, and grinding to obtain modified gelatin.

[0013] By adopting the above technical scheme, the addition of hydrochloric acid can adjust the pH value of the mixed solution to keep it near the isoelectric point of gelatin, which helps the stability and solubility of the gelatin molecules. Trimethylamine oxide can play a certain buffering role in the solution, helping to maintain the stability of the pH value and prevent changes in the protein structure caused by pH fluctuations.

[0014] Quaternary ammonium salts can significantly increase the interlayer spacing of graphene oxide by non-covalent interactions with functional groups such as carboxyl and hydroxyl groups on the surface of graphene oxide, thereby achieving intercalation modification of graphene oxide, which not only improves the dispersibility of graphene oxide in organic media, but also enhances its mechanical strength.

[0015] When quaternary ammonium salt-modified graphene oxide, gelatin solution and modified starch are mixed, quaternary ammonium salt-modified graphene oxide can be embedded in the cross-linked structure of gelatin and modified starch, significantly enhancing the mechanical properties of the system, improving the strength and toughness of the system, and improving its thermal stability. When subsequently applied to the pickling solution, the positive charge of the quaternary ammonium salt interacts with the negatively charged groups in gelatin and modified starch, helping to form a stable dispersion system, which can provide an additional protective layer in the pickling solution, reduce the erosion of the substrate by the acidic environment, and at the same time be able to adsorb solid particles dissolved by the pickling solution to prevent the solid particles from re-depositing on the metal surface, thereby improving the cleaning effect.

[0016] Preferably, the mass ratio of gelatin, graphene oxide and modified starch is 1g:20-30mg:0.2-0.3g.

[0017] By adopting the above technical solution, the mass ratio of gelatin, graphene oxide and modified starch is further limited within a certain range, and the stability of modified gelatin is improved. Gelatin helps release metal ions (such as Cr (III)) from the encapsulation of organic macromolecules. The permeation of the chemical promotes the mass transfer rate of acid between the liquid phase and the solid, which is beneficial to the removal of metal ions. Graphene oxide has the function of adsorbing impurities. The surface of graphene oxide is rich in oxygen-containing functional groups such as hydroxyl (-OH) and carboxyl (-COOH). These functional groups can react with -NH in organic matter. 3 , -OH and other functional groups to form hydrogen bonds, thereby quickly adsorbing organic matter. The hydrophilicity and lipophilicity of the modified starch molecules enable them to adsorb oil and impurities on the surface of the steel substrate. When the acid reacts with the steel substrate, the modified starch molecules can help peel these impurities from the surface of the steel substrate, thereby improving the cleaning efficiency. The thickening effect of the modified starch molecules can increase the viscosity of the pickling solution, help the pickling solution stay on the surface of the steel substrate, extend the pickling time, and improve the cleaning effect.

[0018] Gelatin, graphene oxide and modified starch have a synergistic effect, forming a multi-layer protective film on the surface of the steel substrate, effectively reducing the corrosion of the steel substrate by acid. The protein structure of gelatin can be adsorbed on the surface of the steel substrate, and the hydrophobicity of graphene oxide and the hydrophilicity of modified starch work together to enhance the stability and corrosion inhibition effect of the protective film. The hydrophilicity of gelatin and modified starch helps to adsorb and remove oil and impurities on the surface of the steel substrate, while the high specific surface area and oxygen-containing functional groups of graphene oxide can further promote the adsorption and stripping of impurities and improve the cleaning efficiency. The thickening effect of gelatin and modified starch can improve the viscosity of the pickling solution, allowing the pickling solution to stay on the surface of the steel substrate for a longer time, improving the cleaning effect. At the same time, the addition of graphene oxide can increase the stability of the pickling solution and reduce the consumption of the pickling solution.

[0019] Preferably, the preparation method of the modified starch comprises the following steps: dispersing the starch in a sodium hydroxide solution, stirring evenly, drying, grinding until the particle size passes the sieve, and then dispersing it in deionized water, adding maleic anhydride acrylic acid copolymer and a silane coupling agent, stirring at a temperature of 60-65° C. for 2-3 hours, drying, and grinding to obtain the modified starch.

[0020] By adopting the above technical solution, the presence of sodium hydroxide destroys the hydrogen bonds between starch molecules, making starch molecules more easily dispersed in water, forming a more stable solution, and improving the solubility of starch in water. Silane coupling agent can improve the compatibility between starch and maleic anhydride acrylic acid copolymer, improve the mechanical properties of the starch system, and the combination of maleic anhydride acrylic acid copolymer and starch, as well as the addition of silane coupling agent, can enhance the strength, toughness, heat resistance and thixotropy of the material, and the obtained starch has good adhesiveness, thickening, heat resistance and wear resistance.

[0021] In subsequent applications in pickling liquids, maleic anhydride acrylic acid copolymers have good dispersibility and chelating ability, and can combine with metal ions in the pickling liquid to prevent them from redepositing on the surface of the steel plate. The thickening effect of starch improves the rheological properties of the pickling liquid, allowing it to form a more stable liquid film on the surface of the steel plate, thereby improving the cleaning effect. The addition of silane coupling agents can enhance the bonding of these materials with the surface of the steel plate, further improving the adhesion and cleaning effect of the cleaning liquid.

[0022] Preferably, the preparation method of the modified loofah fiber comprises the following steps: (1) soaking the loofah in hydrogen peroxide for 1-2h, washing, drying, then pulverizing, redispersing in magnesium sulfate solution, stirring for 20-30min, drying, and obtaining a pre-treated loofah; (2) Disperse the glass fibers in deionized water, clean them ultrasonically, and then soak them in TiCl 4 In aqueous solution, stirring at 70-75°C for 2-3h, washing with water, and drying to obtain pretreated glass fiber; (3) dispersing the pretreated loofah in step (1) in deionized water, adding the pretreated glass fiber in step (2), adding modified chitosan, stirring at a temperature of 70-75° C. for 1-2 h, and drying to obtain modified loofah fiber.

[0023] By adopting the above technical scheme, hydrogen peroxide is used as a bleaching agent to effectively remove pigments and impurities on the surface of the loofah, improve its whiteness, and then mixed with a magnesium sulfate solution. The magnesium sulfate solution can penetrate into the fiber structure of the loofah, improve the flexibility, elasticity, water absorption and antiseptic effect of the loofah, and facilitate subsequent mixing with other components.

[0024] Soak glass fiber in TiCl 4 In aqueous solution, TiCl 4 Treat the surface of glass fiber, enhance the adhesion of glass fiber, load on the surface of glass fiber, improve the strength of glass fiber, and help better bonding with other components later.

[0025] Pretreated loofah, pretreated glass fiber and modified chitosan are mixed. Glass fiber can be loaded on the surface and pores of loofah. Modified chitosan has viscosity, which makes glass fiber stably adhere to the surface of loofah, enhancing the mechanical properties, oil absorption and adsorption properties and biocompatibility of loofah. It is subsequently applied to pickling liquid to enhance the physical cleaning effect of pickling liquid. Loofah fiber has a natural porous structure, which can increase the contact area between the cleaning liquid and the steel plate surface, while the hardness and strength of glass fiber can provide additional mechanical scraping force to help remove rust and dirt on the surface of the steel plate. In addition, modified chitosan has good colloidal stability and buffering capacity, which improves the stability of pickling liquid and prevents the rapid consumption of acid during pickling, thereby extending the service life of the cleaning liquid.

[0026] Preferably, the mass ratio of the loofah sponge, glass fiber and modified chitosan is 1:0.5-0.8:0.1-0.2.

[0027] By adopting the above technical scheme, the mass ratio of loofah, glass fiber and modified chitosan is further limited within a certain range, and the comprehensive performance of loofah is improved. The physical effect of loofah and glass fiber, combined with the chemical effect of chitosan, can promote the formation of a uniform microstructure on the surface of the steel plate, which is beneficial to the subsequent coating and anti-corrosion treatment, and improves the corrosion resistance and service life of the steel plate. In addition, the softness of loofah and the buffering effect of modified chitosan can reduce the damage to the surface of the steel plate during the pickling process, avoid damage to the surface of the steel plate caused by excessive cleaning, and maintain the original performance of the steel plate. The combination of loofah, glass fiber and modified chitosan improves the physical cleaning effect of the pickling solution. The loofah fiber has a natural porous structure and the hardness and strength of the glass fiber, which increases the contact area between the cleaning solution and the surface of the steel plate, provides additional mechanical scraping force, and helps remove rust and dirt on the surface of the steel plate.

[0028] Preferably, the preparation method of the modified chitosan comprises the following steps: adding chitosan to an acetic acid solution, adding thiosemicarbazide, stirring for 1-2 hours, then adding xanthan gum and nano-titanium dioxide, stirring for 2-3 hours, and drying to obtain the modified chitosan.

[0029] By adopting the above technical solution, chitosan itself has certain antibacterial activity, but its activity is relatively low. By reacting with thiosemicarbazide, chitosan thiosemicarbazide derivatives can be prepared, and the antibacterial activity of such derivatives is significantly improved, and its solubility and stability are improved.

[0030] Xanthan gum and nano-titanium dioxide are subsequently added, and the xanthan gum and chitosan undergo cross-linking reactions to enhance the antibacterial, antioxidant, and sustained-release properties of chitosan. Nano-titanium dioxide can be embedded in the structure of the chitosan system to improve the mechanical and adsorption properties of chitosan. It is subsequently applied to the pickling solution to enhance the cleaning effect of the pickling solution on the dirt on the surface of the steel plate. The biocompatibility of chitosan and the special chemical properties of xanthan gum can work synergistically to improve the decontamination ability of the cleaning agent. The addition of nano-titanium dioxide can provide additional photocatalytic activity and help decompose organic pollutants on the surface of the steel plate. At the same time, the addition of nano-titanium dioxide can also form a protective film on the surface of the steel plate to improve the corrosion resistance and antioxidant properties of the steel plate.

[0031] In a second aspect, the present application also provides an environmentally friendly hot-dip galvanizing process, comprising the following steps: (1) Place the steel plate in the above pickling solution and soak for 10-12 minutes to remove the oxide on the surface of the steel plate, then wash with water and set aside; (2) immersing the steel plate obtained in step (1) in a plating agent at a temperature of 63-65° C. for 2-3 minutes for later use; (3) immersing the steel plate obtained in step (2) in zinc solution for 100-110 seconds at a temperature of 470-480° C. for standby use; (4) Immerse the steel plate obtained in step (3) in the passivation solution for 2-3 minutes.

[0032] By adopting the above technical solution, the steel plate is first pickled, which is a process of removing the iron oxide scale (rust) on the surface of the steel plate using a pickling solution. The main function is to clean the surface of the steel plate and provide a clean, oxide-free base for subsequent coating treatment.

[0033] Then it is immersed in the plating agent to form a uniform salt film on the surface of the steel plate to improve the wettability of the steel plate with the molten alloy, reduce the surface tension, and prevent the steel plate surface from being further oxidized during the hot dip plating process.

[0034] The steel plate is then immersed in zinc liquid for galvanizing to form a zinc coating on the surface of the steel plate. The zinc coating can provide good anti-corrosion protection because zinc forms a dense zinc oxide protective film in the air to prevent further oxidation of the steel plate.

[0035] Finally, it is immersed in the passivation solution to form a passivation film on the surface of the zinc coating to improve its corrosion resistance and decorative properties. The passivation film can prevent the zinc coating from forming white rust in a humid environment and extend the service life of the steel plate.

[0036] Preferably, the plating assistant consists of zinc chloride, hexadecyltrimethylammonium bromide, sodium phosphate, water and oxalic acid.

[0037] By adopting the above technical solution, zinc chloride can dissolve the residual oxides on the metal surface, clean the surface of the steel plate, improve its surface activity, and provide a good adhesion basis for the subsequent coating. Hexadecyltrimethylammonium bromide can reduce the surface tension, improve the wettability of the plating solution to the metal surface, and help remove grease and dirt on the metal surface to ensure uniform coating. Sodium phosphate can be used as a buffer to adjust the pH value of the plating solution to ensure the stability and uniformity of the coating. Oxalic acid, as a chelating agent, can form a stable complex with metal ions, which helps to control the growth rate and morphology of the coating and improve the density and adhesion of the coating.

[0038] In summary, this application has the following beneficial effects: 1. The synergistic combination of nonylphenol polyoxyethyl ether and sodium dodecyl sulfate in this application can reduce the surface tension of water, improve the wettability of the pickling solution on the metal surface, help the pickling solution to cover the metal surface more evenly, promote the pickling solution to penetrate into the tiny gaps and holes on the metal surface, ensure that all areas can be exposed to the acid, accelerate the chemical reaction between the acid and the metal oxide, and increase the pickling speed.

[0039] 2. The modified gelatin in this application can be used as a corrosion inhibitor, which forms a protective film on the metal surface to reduce the direct erosion of the acid in the pickling solution on the metal, thereby protecting the metal surface from excessive corrosion, controlling the corrosion rate during the pickling process, and protecting the metal substrate.

[0040] 3. The modified loofah fiber in this application has a natural porous structure and can be used as a physical support material for filtering and supporting in the pickling solution. During the pickling process, the modified loofah fiber can capture and filter out solid particles dissolved by the pickling solution, such as metal oxides, rust, etc., to prevent them from redepositing on the metal surface, thereby improving the cleaning effect. DETAILED DESCRIPTION

[0041] The present application is further described in detail below with reference to the embodiments.

[0042] The raw materials used in the examples and comparative examples can all be obtained commercially.

[0043] Preparation example of modified gelatin Preparation Example 1-1 The preparation method of modified gelatin comprises the following steps: (1) adding hydrochloric acid to a gelatin aqueous solution to adjust the pH of the solution to 5, then stirring the solution at 60° C., adding 0.005 kg of trimethylamine oxide to obtain a gelatin solution; wherein 1 kg of gelatin is dispersed in 2 L of water to obtain a gelatin aqueous solution; (2) dispersing graphene oxide in 6L ammonia solution, adjusting the pH of the solution to 9, adding 45g of quaternary ammonium salt, stirring and reacting, centrifuging and drying to obtain quaternary ammonium salt-modified graphene oxide, wherein the quaternary ammonium salt is hexadecyltrimethylammonium bromide; (3) dispersing the quaternary ammonium salt-modified graphene oxide of step (2) in the gelatin solution of step (1), adding modified starch, stirring at a temperature of 70° C. for 2 h, drying, and grinding to obtain modified gelatin.

[0044] The mass ratio of gelatin, graphene oxide and modified starch is 1g:20mg:0.3g.

[0045] The preparation method of modified starch comprises the following steps: dispersing 1 kg of starch in 2 L of sodium hydroxide solution with a mass fraction of 10%, stirring evenly, drying, grinding to a particle size of more than 200 mesh, and then dispersing in 2.2 L of deionized water, adding 0.08 kg of maleic anhydride acrylic acid copolymer and 0.1 kg of silane coupling agent KH-550, stirring at a temperature of 65° C. for 3 h, drying, and grinding to obtain modified starch; wherein the maleic anhydride acrylic acid copolymer is purchased from Nanxing Chemical (Jiangsu) Co., Ltd.

[0046] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), graphene oxide is not added.

[0047] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no modified starch is added.

[0048] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of gelatin, graphene oxide and modified starch is 1g:30mg:0.2g.

[0049] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of gelatin, graphene oxide and modified starch is 1g:1mg:0.6g.

[0050] Preparation Example 1-6 The difference from Preparation Example 1-1 is that in the preparation method of the modified starch, no maleic anhydride acrylic acid copolymer is added.

[0051] Preparation Example 1-7 The difference from Preparation Example 1-1 is that in the preparation method of the modified starch, no silane coupling agent KH-550 is added.

[0052] Preparation example of modified loofah fiber Preparation Example 2-1 The preparation method of modified loofah fiber comprises the following steps: (1) soaking 1.2 kg of loofah in 2 L of 3% hydrogen peroxide for 1.5 h, washing, drying, and then crushing, and then dispersing in 1.8 L of 20% magnesium sulfate solution, stirring for 25 min, and drying to obtain a pretreated loofah; (2) The glass fibers were dispersed in 2 L of deionized water, ultrasonically cleaned, and then immersed in 2.4 L of 1.2 M TiCl 4 The solution was stirred at 75°C for 2.5 h, washed with water and dried to obtain pretreated glass fibers; (3) Dispersing the pretreated loofah in step (1) in 5 L of deionized water, adding the pretreated glass fiber in step (2), adding modified chitosan, stirring at a temperature of 75° C. for 1.5 h, and drying to obtain modified loofah fiber.

[0053] The mass ratio of loofah sponge, glass fiber and modified chitosan is 1:0.5:0.1.

[0054] The preparation method of modified chitosan comprises the following steps: adding 1 kg chitosan to 2 L acetic acid solution with a mass fraction of 1%, adding 0.002 kg thiosemicarbazide, stirring for 2 hours, then adding 0.03 kg xanthan gum and 0.2 kg nano titanium dioxide, stirring for 3 hours, and drying to obtain modified chitosan.

[0055] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no glass fiber is added.

[0056] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (3), no modified chitosan is added.

[0057] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of loofah sponge, glass fiber and modified chitosan is 1:0.8:0.2.

[0058] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of loofah sponge, glass fiber and modified chitosan is 1:0.1:0.6.

[0059] Preparation Example 2-6 The difference from Preparation Example 2-1 is that no xanthan gum is added in the preparation method of modified chitosan.

[0060] Preparation Example 2-7 The difference from Preparation Example 2-1 is that in the preparation method of modified chitosan, no nano titanium dioxide is added. Example

[0061] Example 1 A pickling solution comprises the following raw materials by weight: 30 kg of hydrochloric acid, 15 kg of formic acid, 2 kg of nonylphenol polyoxyethyl ether, 10 kg of sodium dodecyl sulfate, 2 kg of sodium carbonate, 3 kg of hexamethylenetetramine, 110 kg of water, and a wetting agent.

[0062] The wetting agent includes the following raw materials by weight: 8 kg of hydroxyethylidene diphosphonic acid, 6 kg of modified gelatin, and 8 kg of modified loofah fiber.

[0063] The preparation method of the pickling solution comprises the following steps: mixing hydrochloric acid, formic acid, nonylphenol polyoxyethyl ether, sodium dodecyl sulfate, sodium carbonate, a wetting agent, hexamethylenetetramine and water, stirring evenly to obtain a pickling solution; placing a steel plate in the pickling solution, soaking for 12 minutes, removing oxides on the surface of the steel plate, washing with water, and setting aside; the size of the steel plate is 1.0m×0.9m×0.5m.

[0064] The modified gelatin was prepared by using Preparation Example 1-1; and the modified loofah fiber was prepared by using Preparation Example 2-1.

[0065] Example 2 A pickling solution, which differs from Example 1 in that it comprises the following raw materials, by weight: 40 kg of hydrochloric acid, 20 kg of formic acid, 1 kg of nonylphenol polyoxyethyl ether, 6 kg of sodium dodecyl sulfate, 4 kg of sodium carbonate, 5 kg of hexamethylenetetramine, 120 kg of water, and a wetting agent.

[0066] The wetting agent includes the following raw materials by weight: 5 kg of hydroxyethylidene diphosphonic acid, 3 kg of modified gelatin, and 10 kg of modified loofah fiber.

[0067] Example 3 A pickling solution, which is different from Example 1 in that the modified gelatin is prepared using Preparation Example 1-2.

[0068] Example 4 A pickling solution, which is different from Example 1 in that the modified gelatin is prepared using Preparation Examples 1-3.

[0069] Example 5 A pickling solution, which is different from Example 1 in that the modified gelatin is prepared using Preparation Examples 1-4.

[0070] Example 6 A pickling solution, which is different from Example 1 in that the modified gelatin is prepared using Preparation Examples 1-5.

[0071] Example 7 A pickling solution, which is different from Example 1 in that the modified gelatin is prepared using Preparation Examples 1-6.

[0072] Example 8 A pickling solution, which is different from Example 1 in that the modified gelatin is prepared using Preparation Examples 1-7.

[0073] Example 9 A pickling solution, which is different from Example 1 in that the modified loofah fiber is prepared using Preparation Example 2-2.

[0074] Example 10 A pickling solution, which is different from Example 1 in that the modified loofah fiber is prepared using Preparation Example 2-3.

[0075] Embodiment 11 A pickling solution, which is different from Example 1 in that the modified loofah fiber is prepared using Preparation Examples 2-4.

[0076] Example 12 A pickling solution, which is different from Example 1 in that the modified loofah fiber is prepared using Preparation Examples 2-5.

[0077] Embodiment 13 A pickling solution, which is different from Example 1 in that the modified loofah fiber is prepared using Preparation Examples 2-6.

[0078] Embodiment 14 A pickling solution, which is different from Example 1 in that the modified loofah fiber is prepared using Preparation Examples 2-7.

[0079] Comparative Example Comparative Example 1 A pickling solution, which is different from Example 1 in that modified gelatin is not added.

[0080] Comparative Example 2 A pickling solution, which differs from Example 1 in that the modified gelatin is replaced by an equal amount of gelatin.

[0081] Comparative Example 3 A pickling solution, which differs from Example 1 in that no modified loofah fiber is added.

[0082] Comparative Example 4 A pickling solution, which is different from Example 1 in that the modified loofah fiber is replaced by an equal amount of loofah fiber.

[0083] Performance testing The pickling solution prepared in Examples 1-14 and Comparative Examples 1-4 was used to immerse 304 stainless steel in pickling treatment, and the samples after pickling treatment were tested for corrosion resistance. The corrosion resistance test was a neutral salt spray test, and the test standard was based on GB 6458-1986.

[0084] Calculate the weight loss rate of 304 stainless steel after pickling (reflecting the dissolution rate), weight loss rate = (weight before pickling - weight after pickling) / weight before pickling × 100%.

[0085] The surface brightness and glossiness were measured by a gloss tester from BYK Group, Germany; the test results are shown in Table 1.

[0086] Table 1 Test data of embodiments and comparative examples As can be seen from Table 1, the pickling solution prepared in Examples 1-2 of the present application has a good cleaning effect for cleaning the steel plate. Among them, the surface state of Example 1 on the first day is silvery white luster and uniform color. The neutral salt spray test is carried out for 152 hours, the weight loss rate is 0.0923%, the surface gloss is 4.2, and the surface brightness is 56, indicating that the steel plate cleaned with the pickling solution of the present application has good corrosion resistance, the pickling solution has low corrosiveness to the steel plate, and the obtained steel plate surface has gloss and brightness. The pickling solution can more effectively remove dirt on the metal surface and improve the cleaning effect and efficiency.

[0087] The steel plate after pickling in Example 1 was galvanized. The steel plate was first immersed in a plating agent at a temperature of 65°C for 3 minutes; then immersed in 150kg zinc solution for 100 seconds at a immersion temperature of 480°C; finally, the steel plate was immersed in a passivation solution for 3 minutes.

[0088] The passivation solution is a chromium-free passivation solution, and the plating aid is composed of 15 kg zinc chloride, 7 kg hexadecyltrimethylammonium bromide, 15 kg sodium phosphate, 38 kg water and 12 kg oxalic acid.

[0089] (1) Perform a bending test on the sample according to GB / T232-2010, and record the zinc layer shedding and zinc layer cracking conditions at a distance of 6 mm from the edge of the sample. (2) Perform a salt spray resistance test on the sample according to GB / 6458-86 "Standard for Neutral Salt Spray Test of Metal Covering Layers". (3) Perform the test according to the testing standard in GB / T5210-2006 "Pull-off Adhesion Test for Paints and Clear Coatings", and use the XH-M adhesion tester as the tensile testing machine.

[0090] The test results show that the zinc layer on the surface of the steel plate has not fallen off and there are no cracks. The corrosion rate in the salt spray resistance test is 1.5% for 300h and the adhesion is 8.2MPa, indicating that the steel plate treated with the hot-dip galvanizing process on the surface of the steel plate in this application has good corrosion resistance and adhesion performance, so that the zinc layer and the steel plate have good adhesion. The surface of the steel plate is cleaned with a cleaning agent, so that the zinc layer is not easy to fall off, thereby extending the service life of the steel plate surface.

[0091] In the preparation method of modified gelatin in Example 3, graphene oxide is not added; in the preparation method of modified gelatin in Example 4, modified starch is not added; in Examples 5-6, the mass ratio of gelatin, graphene oxide and modified starch is changed. As can be seen from Table 1, the test results of neutral salt spray test, weight loss rate, surface gloss and surface brightness of Examples 3-4 are significantly worse than those of Examples 1-2 and Example 5, while the test performance of neutral salt spray test, weight loss rate, surface gloss and surface brightness of Example 6 are better than those of Examples 3-4, but worse than those of Examples 1 and 5, indicating that gelatin, graphene oxide and modified starch have a synergistic effect, forming a multilayer protective film on the surface of the steel substrate, effectively reducing the corrosion of the steel substrate by the acid solution, the protein structure of gelatin can be adsorbed on the surface of the steel substrate, and the hydrophobicity of graphene oxide and the hydrophilicity of modified starch work together to enhance the stability and corrosion inhibition effect of the protective film and improve the cleaning efficiency.

[0092] In the preparation methods of the modified starches of Examples 7-8, maleic anhydride acrylic acid copolymer and silane coupling agent are not added respectively. As can be seen from Table 1, the test results of the neutral salt spray test, weight loss rate, surface gloss and surface brightness of Examples 7-8 are significantly worse than those of Examples 1-2, but better than those of Example 4, indicating that the maleic anhydride acrylic acid copolymer has good dispersibility and chelating ability, and can combine with the metal ions in the pickling solution to prevent them from redepositing on the surface of the steel plate. The thickening effect of starch improves the rheological properties of the pickling solution, so that it forms a more stable liquid film on the surface of the steel plate, thereby improving the cleaning effect. The addition of silane coupling agent can enhance the combination of these materials with the surface of the steel plate, further improving the adhesion and cleaning effect of the cleaning solution.

[0093] In the preparation method of the modified loofah fiber in Examples 9-10, glass fiber and modified chitosan are not added respectively. In Examples 11-12, the mass ratio of loofah, glass fiber and modified chitosan is changed. It can be seen from Table 1 that the test results of the neutral salt spray test, weight loss rate, surface gloss and surface brightness of Examples 9-10 are significantly worse than those of Examples 1-2 and Example 11, while the test performance of the neutral salt spray test, weight loss rate, surface gloss and surface brightness of Example 12 are better than those of Examples 9-10, but worse than those of Examples 1 and Example 11, indicating that the physical effect of loofah and glass fiber, combined with the chemical effect of chitosan, can promote the formation of a uniform microstructure on the surface of the steel plate, which is beneficial to subsequent coating and anti-corrosion treatment, and improves the cleaning effect, corrosion resistance and service life of the steel plate.

[0094] In the preparation methods of modified chitosan of Examples 13-14, xanthan gum and nano-titanium dioxide are not added respectively. As can be seen from Table 1, the test results of neutral salt spray test, weight loss rate, surface gloss and surface brightness of Examples 13-14 are significantly worse than those of Examples 1-2, but better than those of Example 10, indicating that the biocompatibility of chitosan and the special chemical properties of xanthan gum work synergistically to improve the decontamination ability of the cleaning agent. The addition of nano-titanium dioxide can form a protective film on the surface of the steel plate, improving the corrosion resistance and oxidation resistance of the steel plate.

[0095] Comparative Examples 1 and 3 do not add modified gelatin and modified loofah fiber, respectively. As can be seen from Table 1, compared with Example 1, the test results of the neutral salt spray test, weight loss rate, surface gloss, and surface brightness of Comparative Examples 1 and 3 are significantly worse than those of Examples 1-2, indicating that modified gelatin has good suspension properties, can help the solid particles generated during the pickling process to remain suspended, prevent them from redepositing on the metal surface, and ensure the cleaning effect. The modified loofah fiber can capture and filter out the solid particles dissolved by the pickling solution, prevent them from redepositing on the metal surface, thereby improving the cleaning effect.

[0096] In Comparative Examples 2 and 4, the modified gelatin is replaced by an equal amount of gelatin, and the modified loofah fiber is replaced by an equal amount of loofah fiber. It can be seen from Table 1 that compared with Example 1, the test results of the neutral salt spray test, weight loss rate, surface gloss, and surface brightness of Comparative Examples 2 and 4 are significantly worse than those of Examples 1-2, but better than those of Comparative Examples 1 and 3, indicating that the modified gelatin and modified loofah fiber of the present application have better cleaning effect, effectively remove dirt on the metal surface, and improve the cleaning effect and efficiency.

[0097] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A pickling solution, characterized in that The invention comprises the following raw materials by weight: 30-40 parts of hydrochloric acid, 15-20 parts of formic acid, 1-2 parts of nonylphenol polyoxyethyl ether, 6-10 parts of sodium dodecyl sulfate, 2-4 parts of sodium carbonate, 3-5 parts of hexamethylenetetramine, 110-120 parts of water and a wetting agent; the wetting agent comprises hydroxyethylidene diphosphonic acid, modified gelatin and modified loofah fiber.

2. A pickling solution according to claim 1, characterized in that: The wetting agent comprises the following raw materials by weight: 5-8 parts of hydroxyethylidene diphosphonic acid, 3-6 parts of modified gelatin, and 8-10 parts of modified loofah fiber.

3. A pickling solution according to claim 1, characterized in that: The preparation method of the modified gelatin comprises the following steps: (1) adding hydrochloric acid to the gelatin aqueous solution to adjust the pH of the solution to 5-6, then stirring the solution at a temperature of 60-65°C, and adding trimethylamine oxide to obtain a gelatin solution; (2) dispersing graphene oxide in an ammonia solution, adjusting the pH of the solution to 8-9, adding a quaternary ammonium salt, stirring the reaction, centrifuging, and drying to obtain quaternary ammonium salt-modified graphene oxide; (3) Dispersing the quaternary ammonium salt-modified graphene oxide of step (2) in the gelatin solution of step (1), adding modified starch, stirring at a temperature of 65-70° C. for 1-2 h, drying, and grinding to obtain modified gelatin.

4. A pickling solution according to claim 3, characterized in that: The mass ratio of the gelatin, graphene oxide and modified starch is 1g:20-30mg:0.2-0.3g.

5. A pickling solution according to claim 3, characterized in that: The preparation method of the modified starch comprises the following steps: dispersing the starch in a sodium hydroxide solution, stirring evenly, drying, grinding until the particles pass the sieve, then dispersing it in deionized water, adding maleic anhydride acrylic acid copolymer and a silane coupling agent, stirring at a temperature of 60-65° C. for 2-3 hours, drying, and grinding to obtain the modified starch.

6. A pickling solution according to claim 1, characterized in that: The preparation method of the modified loofah fiber comprises the following steps: (1) Soaking the loofah in hydrogen peroxide for 1-2 hours, washing, drying, and then crushing, and then dispersing in a magnesium sulfate solution, stirring for 20-30 minutes, and drying to obtain a pretreated loofah; (2) dispersing the glass fiber in deionized water, ultrasonically cleaning it, and then immersing it in a TiCl4 aqueous solution, stirring it at 70-75°C for 2-3 hours, washing it with water, and drying it to obtain pretreated glass fiber; (3) Dispersing the pretreated loofah obtained in step (1) in deionized water, adding the pretreated glass fiber obtained in step (2), adding modified chitosan, stirring at a temperature of 70-75° C. for 1-2 h, and drying to obtain modified loofah fiber.

7. A pickling solution according to claim 6, characterized in that: The mass ratio of the loofah sponge, the glass fiber and the modified chitosan is 1:0.5-0.8:0.1-0.

2.

8. A pickling solution according to claim 6, characterized in that: The preparation method of the modified chitosan comprises the following steps: adding chitosan into acetic acid solution, adding thiosemicarbazide, stirring for 1-2 hours, then adding xanthan gum and nano titanium dioxide, stirring for 2-3 hours, and drying to obtain the modified chitosan.

9. An environmentally friendly hot-dip galvanizing process, characterized in that: The steps include: (1) placing the steel plate in the pickling solution according to any one of claims 1 to 8, soaking for 10 to 12 minutes to remove oxides on the surface of the steel plate, washing with water, and setting aside; (2) Immerse the steel plate obtained in step (1) in a plating agent at a temperature of 63-65° C. for 2-3 minutes and set aside; (3) immersing the steel plate obtained in step (2) in zinc solution for 100-110 seconds at a temperature of 470-480° C. for standby use; (4) Immerse the steel plate obtained in step (3) in the passivation solution for 2-3 minutes.

10. An environmentally friendly hot-dip galvanizing process according to claim 9, characterized in that: The plating assistant consists of zinc chloride, hexadecyltrimethylammonium bromide, sodium phosphate, water and oxalic acid.